Selecting the structure and formats of data in the videoconferencing system - Zhuraev A. K. (Modern conceptions of processes and technology: problems, states and perspectives)
this article contains a puncturing scheme, a similar model for building several levels of protocols. The interface of physical media (channels) providing reliable data transit through a physical channel.
Keywords: протокол; сбор информации; синхронизация; synchronization; connections; protocol; information gathering; подключения